A multi-system weighted fusion method to improve measurement accuracy of structured light 3D profilometry. (1st May 2022) - Xing, Chao; Huang, Junhui; Wang, Zhao; Gao, Jianmin
Abstract: Improving the accuracy of three-dimensional profile measurement based on binary coded structured light for complex surfaces is a challenge. A new method of weighted fusion using multiple systems is presented to reduce the measurement errors due to the stripe grayscale asymmetry. It is based on the analysis of stripe center deviation related to the surface normal and the directions of incident and reflected rays. First, the stripe center deviation model is established according to the geometric relationship between the stripe center deviation and the incident and reflected angles at any measured point. The influence of each variable on stripe center deviation is analyzed, and three subsystems are formed by a binocular structured light framework to achieve multiple measurements based on the influence regularity. Then, in order to improve the measurement accuracy, different weights are assigned to the measured point in the different subsystems according to the stripe center deviation model and its relationship with the measurement error, and the weighted data from the different subsystems are fused. Experiments are carried out to validate the presented method, and the experimental results demonstrate that it effectively improves the measurement accuracy of complex surfaces. The measurement accuracy is improved by about 27% compared with the conventional method.